AB0736 Secukinumab Significantly Improves Physical Function, Quality of Life, and Work Productivity Through 52 Weeks in Subjects with Active Ankylosing Spondylitis in the Phase 3 Measure 2 Study. (9th June 2015) - Deodhar, A.; Sieper, J.; Emery, P.; Porter, B.; Andersson, M.; Richards, H.
Abstract : Background: Interleukin (IL)-17A is implicated in the pathogenesis of ankylosing spondylitis (AS), 1 and inhibition of this cytokine with secukinumab, a human anti–IL-17A monoclonal antibody, has previously demonstrated rapid reduction in the signs and symptoms of AS at Week (Wk) 16 in a phase 3 trial (MEASURE 2; NCT01649375 ). 2 Objectives: To evaluate the impact of subcutaneous (s.c.) secukinumab on patient-reported outcomes (PROs) at 16 and 52 wks in the randomized, double-blind, placebo-controlled, MEASURE 2 study. Methods: 219 adults with active AS, despite therapy with nonsteroidal anti-inflammatory drugs, were randomized to receive s.c. secukinumab 150 mg, 75 mg, or placebo (PBO) at baseline, Wk 1, 2, and 3, and then every 4 wks starting at Wk 4. At Wk 16, subjects randomized to PBO at baseline were re-randomized to receive secukinumab 150 mg or 75 mg every 4 wks. PROs were measured every 4 wks using the following questionnaires: Short Form-36 Health Survey (SF-36), EuroQoL (EQ-5D), AS Quality of Life (ASQoL), Functional Assessment of Chronic Illness Therapy – Fatigue (FACIT-Fatigue) and Work Productivity and Activity Impairment – General Health (WPAI-GH). SF-36 Physical Component Summary (SF-36 PCS) and ASQoL were predefined secondary endpoints, assessed at Wk 16 as part of a hierarchical statistical testing strategy with adjustment for multiplicity. Other endpoints were exploratory. Results: Demographics and disease severity were balanced across groups at baseline, with subjects experiencing moderate to severe levels of fatigue and impaired health-related quality of life (QoL). At Wk 16, secukinumab 150 mg significantly improved SF-36 PCS and ASQoL scores vs PBO; improvements in these parameters were observed from Wk 4, the first time point of measurement. Improvements vs PBO were also noted in FACIT-Fatigue at Wk 16 (Table ). Mean changes from baseline with secukinumab at Wk 16 were greater than the minimum clinically important difference (MCID) for SF-36 PCS, ASQoL and FACIT-Fatigue (Table ). Reductions in WPAI-GH were also observed with secukinumab vs PBO at Wk 16. Improvements in PROs from baseline were sustained or increased from Wk 16 through Wk 52 (Table ). Conclusions: In subjects with active AS, secukinumab 150 mg provided rapid and sustained improvements in PROs, including fatigue, general and AS-specific QoL measures, and illness-associated reductions in work productivity. References: Yeremenko N, et al. Curr Opin Rheumatol 2014;26:361–70. Sieper J, et al. Arthritis Rheumatol 2014;66(11 Suppl):S232 Acknowledgements: Medical writing support was provided by Rachel Mason at Seren Communications (Tytherington, UK), and was funded by Novartis. Disclosure of Interest: A. Deodhar Grant/research support from: AbbVie, Celgene, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Celgene, Janssen, Novartis, Pfizer, and UCB, J. Sieper Grant/research support from: AbbVie, Pfizer, and Merck, Consultant for: AbbVie, Pfizer, Merck, UCB, and Novartis, Speakers bureau: AbbVie, Pfizer, Merck, and UCB, P. Emery Consultant for: AbbVie, BMS, Merck, Novartis, Pfizer, Roche, and UCB, B. Porter Shareholder of: Novartis, Employee of: Novartis, M. Andersson Employee of: Novartis, H. Richards Employee of: Novartis